3a+b+2a+5b=( + )+( + )= +
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 21:54:24
3a+b+2a+5b=(+)+(+)=+3a+b+2a+5b=(+)+(+)=+3a+b+2a+5b=(+)+(+)=+3a+b+2a+5b=(3a+2a)+(b+5b)=5a+6b3a+b+2a+5
3a+b+2a+5b=( + )+( + )= +
3a+b+2a+5b=( + )+( + )= +
3a+b+2a+5b=( + )+( + )= +
3a+b+2a+5b=(3a +2a )+( b+ 5b)=5a +6b
3a+b+2a+5b=(3a +2a )+( b+ 5b)=5a +6b
已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?
已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?
若a-b/a+b=4,求5a-b/a+b- a+b/2(a-b)
合并同类项:2(a+b)-5(b+a)+a+b=( )A.a-b B.-(a+b) C.-2(a+b) D.-a+b
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
a+b/2a-b=2 则3(a+b)/5(2a-b)-2a-b/3(a+b)=
当a+b分之2b-a=5时,求代数式a+b分之2*(2a-b)+2a-b分之3(a+b)
5(a+b)-3(a-b)=2 2(a+b)+5(a-b)=7
(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?
3a+b+2a+5b=( + )+( + )= +
2b²+(a+b)(a-b)-(a-b)²,其中a=-3
4(a+b)-5/2(a+b)^2+3(a+b)-3/2(a+b)^2=?怎样算?
已知2(a+1)(a-1)-(a+b)(a-b)-5b=3,求(a+2b)(a-2b)的值
先化简再求值 (a-2b)(a²+2ab+4b²)-a(a-5b)(a+3b),其中a=-1,b=2
A=B+B+B+B+B+B+B+B+B+B+B+B+B+B+B A-B×3=C C+2×7+2=1A=B+B+B+B+B+B+B+B+B+B+B+B+B+B+BA-B×3=CC+2×7+2=148148-(C-32)=DA,B,C,D各是多少?
(a-2b)(a+2b)-(a-5b)(a+3b),当a=-1,b=1
已知|a|=2 ,|b|=5 ,a×b=-3 ,求|a+b|,|a-b| a,b为向量
/a+b-5/+(a-b+3)^2=0,那么a^2+b^2=( )